Niche-specific association of Aeromonas ribotypes from human and environmental origin - Bauab, Taís Maria [UNESP]; Levy, Carlos Emílio; Rodrigues, Josias [UNESP]; Falcão, Deise Pasetto [UNESP] (Wiley, 2003)
A total of 88 Aeromonas isolates from distinct locations and sources (39 from extraintestinal infections, 31 from diarrhoeic, ten from non-diarrhoeic faeces, all human, and eight from fresh water) were subjected to phenospecies identification, serotyping, ribotyping and detection of some virulence markers. The strains belonged to four different phenospecies marked by 19 O serogroups and 38 ribotypes. No strong correlation between these parameters was found, and no group, as defined by the typing methods, could be characterized with a particular set of virulence markers. There was a clear association of ribotypes with the source of the strains. Cluster analysis allowed the identification of a complex of ribotypes belonging to distinct but related sources, including clinical and environmental isolates. These results suggest that ribotyping may be an epidemiological tool suitable for the study of Aeromonas infections.
Keywords: Aeromonas; Ribotyping; Serotyping; Virulence markers; virulence factor; bacterial strain; bacterium identification; bacterium isolate; cluster analysis; environment; nonhuman; protein analysis; ribotyping; serotyping; Animals; Bacterial Adhesion; Bacterial Toxins; Blotting, Southern; Cercopithecus aethiops; Cluster Analysis; DNA Fingerprinting; DNA, Bacterial; Gram-Negative Bacterial Infections; Hela Cells; Humans; Polymorphism, Restriction Fragment Length; Variation (Genetics); Vero Cells; Virulence; Water Microbiology; Bacteria (microorganisms); Negibacteria